Investigation of Antimicrobial Susceptibility Patterns and blaVIM -metallo-β-lactamase Gene in Clinical Samples of Klebsiella pneumoniae - Alkhafaji, Asaad; Soleimani, Neda; Mousa, Hind (University of Thi-Qar Journal of Science, 2023)
Multidrug resistance is a widespread issue that plays an important role in disease outcome. This study was designed to isolate Klebsiella pneumonia in different clinical specimens and detected their Antibiotic resistance profile. A total of 319 samples were collected from various clinical specimens for both genders and different ages. The samples were streaked on the blood and MacConkey agars.  The bacterial growth identified using biochemical tests and Vitek®2 systems to confirm it. Also, the Vitek®2 system was used to detect the antibiotic sensitivity. Out of 319 clinical samples, K. pneumonia was identified in 67 (21%) cases. The highest isolation rate was in urine 25(37.3%), followed by sputum 13(19.4%), and the least isolation was in CSF with one isolate (1.5%). The results revealed that K. pneumonia isolates were multi-drug resistant pathogens (MDR) with high resistance to Ampicillin (97%) and 85% for piperacillin.The PCR results revealed blaVIM- genes frequency was 20 (30%). K. pneumonia is one of the bacteria that cause urinary tract infections, and it is a widespread multidrug-resistant pathogen, and blaVIM- producing K. pneumoniae are found in clinical samples at Thi-Qar hospitals. Therefore, monitoring the administration of antibiotics and their rational use is necessary to reduce antimicrobial resistance and treatment failure.